SOCIAL ECONOMIC OBSTACLES EDUCATION OF FISHERMEN’S CHILDREN DURING THE COVID-19 PANDEMIC - Khodijah, . (PUPIL: International Journal of Teaching, Education and Learning, 2021)
This research focuses on the socio-economic barriers to education for fishermen's children during the COVID-19 pandemic, as well as teacher's strategies to overcome them. The research method used a qualitative descriptive approach. Collecting data using the method of observation and semi-structured interviews with a zoom meeting application to respondents. The school sample was determined purposively, namely the public Madrasah Ibtidaiyah Negeri (MIN) 1 Berakit Village, Bintan Regency, Riau Islands Province, Indonesia. The research respondents consisted of the principal, teachers, students, and representatives of the parents. The findings of this study reveal that fishermen's children experience socio-economic obstacles in the learning process during the COVID-19 pandemic, which is caused by factors of income, education, and their parents' occupation as fishermen. As fishermen, the parents of students have relatively low income and education levels. So that online learning does not take place effectively. The potential of the coastal environment which has beautiful and clean natural characteristics turns out to be able to be a solution in overcoming the socio-economic obstacles of fishermen's children following online learning. Teachers have used it as a collaborative and communicative learning media during the COVID-19 pandemic.